2014
DOI: 10.1093/rpd/ncu182
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference levels and patient doses in computed tomography examinations in Greece

Abstract: The purpose of this study is to present a national survey that was performed in Greece for the establishment of national Dose Reference Levels (DRLs) for seven common adult Computed Tomography (CT) examinations. Volumetric computed tomography dose index and dose-length product values were collected from the post-data page of 65 'modern' systems that incorporate tube current modulation. Moreover, phantom dose measurements on 26 'older' systems were performed. Finally, the effective dose to the patient from a ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 3 publications
2
7
0
2
Order By: Relevance
“…For an axial scan with pitch of 1 and scan length of 22 cm, the DLP values for three different scan setting of Table were 163.68, 306.24, and 534.6, at tube voltages of 80, 100, and 120 kVp, respectively. The amount of DLP values of this study are within the range reported by other authors …”
Section: Methodssupporting
confidence: 91%
“…For an axial scan with pitch of 1 and scan length of 22 cm, the DLP values for three different scan setting of Table were 163.68, 306.24, and 534.6, at tube voltages of 80, 100, and 120 kVp, respectively. The amount of DLP values of this study are within the range reported by other authors …”
Section: Methodssupporting
confidence: 91%
“…Table 8 and Figure 5 summarize the results for the trunk (chest; abdomen and pelvis; chest, abdomen, and pelvis) examinations for median-size patients. Table 9 shows that the U.S. DRLs are not markedly different from those in other countries (11)(12)(13)(19)(20)(21)(22)(23)(24)(25).…”
Section: Resultsmentioning
confidence: 95%
“…There are considerable DRLs and benchmarks available internationally for our comparison. (Table 2) [8,9,12,20,[22][23][24][25][26][27][28][29][30]. Our institutional median values, also known as, our FRL are considerably lower than all other countries and well below our NDRL.…”
Section: Discussionmentioning
confidence: 86%